Implementasi Pengaturan Perlindungan Hak Asasi Manusia di Indonesia - Endri Endri (Jurnal Selat, 2014)
Human rights are basic rights that should be granted to everyone, because it is the nature of the by God to man. In Indonesia, the protection of human rights spread in product legislation, however the practice field find the constraints that hamper the protection of human rights itself. Implementation of human rights enforcement much focused on perpetrators, while the part of the victim has not been getting good attention. Keywords: Implementation Arrangements Protection Human Rights